VARIATION OF SUPERPLASTICIZER AMOUNT ON CONCRETE COMPRESSIVE STRENGTH - Layang, Samuel; Wiratno; Henra Hartako; Rido (BALANGA: Jurnal Pendidikan Teknologi dan Kejuruan, 2023)
This study aims to determine the effect of the addition of superplasticizer in concrete mixtures on compressive strength. To achieve this goal, a laboratory study was conducted using 12 cylindrical specimens with a diameter of 150 mm and a height of 300 mm. There are three variations of superplastcizer addition and one variation of concrete without superplastcizer addition as control. The concrete cylinders were tested at 14 days. The coarse aggregate used is a combination of 2 types of aggregates, namely Banjarmasin Stone (50%) and Merak Stone (50%).From the test results, the average compressive strength of concrete without using superplasticizer was 27.10 MPa. The compressive strength of concrete using superplasticizer (mix design results) is 37.18 MPa. For concrete that uses less superplasticizer (reduced by 1% from the mix design results) results in a compressive strength of 34.06 MPa. While for concrete that uses more superplasticizer (increased by 1% from the results of the mix design) gives a compressive strength of 37.02 MPa. Concrete that uses superplasticizer has a greater compressive strength value than concrete without superplasticizer